Biosensors- types and application in food processing industry - Aggarwal, Sunita; Sehgal, Shalini; Tandon, Akanksha Wadehra (Journal of Postharvest Technology, 2024)
The hazard identification and characterization are important steps in the microbial food safety risk assessment methodology. There have been various  molecular techniques for the identification of microorganisms like Fluorescence microscopy, PCR and hybridization. The rRNA detection is suitable for  detecting metabolically active bacterial populations. Genetic fingerprinting is applicable to only bacterial pure cultures. Therefore, new detection and real  time methods are required for better assessment of the food products. The aim is to increase the detection specificity, reduction in the time of analysis,  application on a large scale and decrease the resource requirement as in the molecular methods. There is a need for the development of automated  techniques that will allow thorough and high output analysis of large number of samples. This will greatly facilitate the industrial microbial studies at all  levels. The real time monitoring of the food samples using biosensors is a promising field and being explored for their utility for various food categories.  This review explores types of biosensors, their working principles and their application in food fermentation and detection of hazards like allergens,  antibiotics, heavy metals. It also highlights the advantages and the scope of further improvement in the existing technology.
Keywords: Analyte; biosensors; detection; monitoring; risk assessment